До питання формування узгодженого розвитку підприємств продовольчого комплексу - Ізмодєнова, Н.К. (Культура народов Причерноморья, 2014)
Досліджено сутність та необхідність формування узгодженого розвитку підприємств
продовольчого комплексу. Актуальною є реалізація основних положень стосовно до агропродовольчого
комплексу як складної соціально-економічної системи. У світовій науці уся зростаюча увага
приділяється дослідженню проблем взаємодії суспільства й природи, взаємовпливу природного
середовища й антропогенної діяльності. У результаті реформ у українському агропродовольчому
комплексі відбулися істотні соціально-економічні перетворення. Ефективність системи регулювання
укладається в створенні умов для стійкого економічного розвитку. Наукове обґрунтування стратегії
сталого розвитку агропродовольчого комплексу країни вимагає чіткого визначення відповідних
критеріїв, що відображають мінливі внутрішні й зовнішні умови. Исследована сущность и необходимость формирования согласованного развития
предприятий продовольственного комплекса. Актуальной является реализация основных положений
относительно агропродовольственного комплекса как сложной социально-экономической системы. В
мировой науке возрастает внимание исследованию проблем взаимодействия общества и природы,
взаимовлияния природной среды и антропогенной деятельности. В результате реформ в украинском
агропродовольственном комплексе состоялись существенные социально-экономические преобразования.
Эффективность системы регулирования заключается в создании условий для стойкого экономического
развития. Научное обоснование стратегии постоянного развития агропродовольственного комплекса
страны требует четкого определения соответствующих критериев, которые отображают
непостоянные внутреннее и внешнее условия. The essence and necessity of forming the agreed development of the enterprises of the food complex
are under investigation. Up to date is the realization of the basic statements concerning the agricultural complex
as a compound socio-economic system. In the world science attention to investigation of the problem of
interaction of environmental surrounding and anthropogenic activity increases. Because of the reforms in
Ukrainian agricultural complex, the major socio-economical transformations took place. The effectiveness of the
regulation of the system lies in the creation of the conditions for the steady economic development. Scientific
grounding of the strategy of the steady development of the agricultural complex of the country demands the
precise definition of the criteria that reflect the unsteady inner and outer conditions. The most important
constituent of the food politics is the supplying of the agreed growth of the agricultural production – the basis of
the supplying the population with food. At the same time, the stability of the dynamics of the production may be
achieved only based on adoption of scientific and technological advance in agricultural sphere and in the fields
that provide it. The adoption of progressive technologies requires sufficient providing of the agricultural branch
with material and technical basis. All it demands the definite ties of agricultural production with other branches
as in the field of providing the material technical basis as also in the field of realization of the agricultural
feedstock and its further processing.